Evaluating the effectiveness of companies managing pension funds based on DEA (Data Envelopment Analysis) - Елена Анатольевна Федорова; Юрий Алексндрович Зеленков; Анастасия Андреевна Ткаченко; Юрий Федорович Федоров (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2017)
This paper features a non-parametric DEA method and its practical applications for the efficiency estimation of the Russian companies managing pension funds. Theoretical aspects of the five DEA models are studied, including: the constant returns to scale model (CRS); increasing, decreasing and varying returns to scale (DRS, IRS and VRS), and the free disposal hull (FDH). A comparative analysis of the models features an example of 39 pension funds management companies from the 2004 to 2016. The efficiency has been estimated taking into account the management companies specific. The financial indicators responsible for the financial activity of the companies have been studied along with those of the pension fund portfolio management. The model under consideration is characterized by one input variable (the investment amount in the first quarter) and three output variables: net assets value (NVA), return on investment (quarterly), and the account balance at a credit organization. The external factors that have impact on the company performance in the sector have been the focus of the recent research, rather than the company efficiency estimation itself.The returns and the risk of the company portfolio, as well as the net assets and the crisis indicators of the economy have been chosen as the qualitative criteria for estimating the efficiency of the companies.The selected DEA algorithm modifications can be used for further investment and management decision making process.